Mineral content in four browse species from Northeastern Mexico - Domínguez Gómez, Tilo Gustavo; Ramírez Lozano, Roque Gonzalo; González Rodríguez, Humberto; Cantú Silva, Israel; Gómez Meza, Marco Vinicio; Alvarado, María del Socorro (Pakistan Botanical Society, Department of Botany, University of Karachi, 2014)
The aim of the present study was to determine and compare macro (Ca, K, Mg, Na and P) and micro (Cu, Fe, Mn and Zn) nutrient foliar content in Acacia amentacea (DC.), Celtis pallida (Torr.), Forestiera angustifolia (Torr.) and Parkinsonia texana (A. Gray). Leaf samples were collected monthly from January throughout December 2009 in China, Linares and Los Ramones counties in the state of Nuevo Leon, Mexico. All nutrients were significantly different among sites, months and species; double and triple interactions were also significant. Among sites, samples from Los Ramones County showed the higher macronutrient content, followed by China and Linares. As for species, Celtis pallida showed the highest values while A. amentacea had the lowest macronutrient content. Micronutrient content showed the following decreasing order: China>Los Ramones>Linares. Parkinsonia texana was characteristically the most abundant in micronutrient content, while, A. amentacea was the poorest in this respect. Regardless of species, site or timing, Ca (total mean = 30 g kg-1), K (15; except A. amentacea), Mg (5.2; except A. amentacea), Na (1.9; only F. angustifolia), Fe (100 mg kg-1), Mn (51; only F. angustifolia) and Zn (35; except A. amentacea) were determined to be present in suitable amounts to meet nutritional requirements of range ruminants, while Na (1.9; except F. angustifolia), P (1.3 g kg-1) and Cu (6 mg kg-1) were marginally deficient throughout the year.